Spontaneous isolated celiac and splenic artery dissection - Brandão, Daniel (2023)
INTRODUCTION: Spontaneous isolated visceral artery dissection is a quite rare condition and designates a dissection that originates in the visceral artery itself with no involvement of the aorta. The objective of this revision article is to summarize the current evidence on this rare pathology. METHODS: A non-systematic literature search was performed using the PubMed database. Only English literature was considered. A narrative review was constructed, with the following headings: epidemiology; etiology; diagnosis; treatment; and follow-up. RESULTS: The celiac trunk is very rarely affected by isolated dissection. Simultaneous isolated celiac and splenic artery dissection are even rarer with less than 50 cases described so far. Even if there are associated with several possible risk factors, their definitive etiology remains unknown. The clinical presentation is quite variable ad most of the patients can be handled medically. Nonetheless, careful follow-up appears to be recommended and endovascular or open surgery should be performed in case of complications. CONCLUSIONS: Spontaneous isolated celiac and splenic artery dissection are very rare and definitive etiology remains unknown. Individualized treatment and careful follow-up are recommended.